PENINGKATAN KAPASITAS MASYARAKAT MELALUI PENYULUHAN DAN PELATIHAN TERPADU BERBASIS POTENSI LOKAL DI KAMPUNG MOKWAM, KABUPATEN MANOKWARI - Budi Santoso; Ludia Theresia Wambrauw; Elfira Kariane Suawa; Meike Meilan Lisangan; Rina Anita Mogea; Agustina Martha Tanatty; Zarima Wibawati; Yustisia Krisna Jati; Jeanifer Gita Tandililing; Amiruddin Amiruddin (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
This community service activity aimed to enhance community capacity through integrated counseling and training based on local potential in Mokwam Village, Mokwam District, Manokwari Regency. The activity was conducted on November 15, 2025, at the Mokwam Village Hall, involving 30 participants consisting of village officials and community members. The methods employed included counseling through interactive lectures, discussions, the use of visual media, and participatory practical training. The materials delivered covered poultry disease management, the production of liquid organic fertilizer based on photosynthetic bacteria, household financial management, and local food processing in the form of cassava chips and pineapple jam. The results of the activity showed an improvement in participants’ knowledge and skills regarding the utilization of local potential in the fields of livestock, agriculture, and household food processing. The high level of participant involvement during discussions and practical sessions indicated that the participatory approach was effective in supporting the transfer of knowledge and skills. This activity also encouraged the more productive and sustainable utilization of local resources, thereby contributing to the improvement of the village community’s economic independence. Therefore, this community service activity was able to enhance the community’s knowledge and skills in utilizing local potential to support the economic self-reliance of the Mokwam Village community.